Floating Lateral Mass Fractures of the Cervical Spine. Issue 18 (15th September 2016) - Manoso, Mark W.; Moore, Timothy A.; Agel, Julie; Bellabarba, Carlo; Bransford, Richard J.
Abstract : Study Design: Level I trauma center case series. Objective: The purpose of this study was (i) to characterize the floating lateral mass (FLM) fracture with the mechanism of injury, anatomical injury pattern, associated vascular injuries, neurological deficits, and key radiographic features; and (ii) to better understand the most effective method of treatment. Summary of Background Data: An uncommon and poorly described subset of unilateral lateral mass fractures is FLM with fractures of the adjacent pedicle and lamina. Methods: Prospectively collected trauma registries were assessed to identify all patients with FLM fractures involving C3 to C7 between January 1, 2007 and December 31, 2012. Results: After institutional review board approval, 60 consecutive cases were identified from the trauma registries. The mean follow-up was 9 months (range 0–42 months). The most common level was C6. The most common mechanism of injury was a high speed motor vehicle accident (45%). Radiographic rotational displacement manifested as an anterolisthesis. CT showed facet joint widening at the level above and below in 63%. Vertebral artery injuries occurred in 22%. Neurological deficits occurred as radiculopathy in 38% and spinal cord injury in 18%. All eight patients, who were treated nonoperatively, developed subluxation despite external immobilization and six patients required surgery. Of the 58 patients treated operatively, 31 (53%) patients underwent a 2 level Anterior Cervical Discectomy and Fusion (ACDF) alone. Nine (15%) patients had one level ACDF, with 83% demonstrating radiographic failure. Posterior fusion alone or combined with ACDF/corpectomy was performed in 6 patients (10%) and 7 patients (12%), respectively. Conclusion: A FLM fracture results from a high energy injury and involves two motion segments. Vertebral artery injuries and neurological deficits frequently occur. Magnetic Resonance demonstrates a significant disc injury in 81% of patients, usually at the lower level. Two level ACDF or Posterior Spinal Instrumented Fusion are effective means of treatment. Level of Evidence: 3